Impacto de la pandemia por coronavirus (COVID-19) en exportaciones de minerales desde Perú hacia China - Valencia Calderon, Romulo Andre (2022)
The context of this study will place us in the COVID-19 pandemic, where the impact on the export of minerals from Peru to China was analyzed. In this scenario, a comparison was made of how the export of minerals from Peru to the Asian country and the Peruvian economy and China are found in 2019. Likewise, this analysis includes data on the minerals exported from our country to China, as well as the Peruvian economy and China. The work is a documentary review of a database of the National Institute of Statistics and Informatics (INEI), the Central Reserve Bank of Peru (BCRP) and other sources and government agencies. The methodology used is based on the use of the documentary record, this thesis compiles real data published by public bodies to be able to compare figures and review the impact of COVID-19 on the economy and therefore on exports. In this case, it was necessary to study it due to the issue of the pandemic, to know what impact this has caused to the Peruvian economy, mainly due to the export of minerals, which are the first export products and in which China is its main client in this area.